Nitrogen management strategies on perennial ryegrass-white clover pastures in the Western Cape Province - Labuschagne, Johan (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD(Agric) (Agronomy))--University of Stellenbosch, 2005.